Remediasi Miskonsepsi Menggunakan Model Learning Cycle 5E Pada Materi Fluida Statis - Inge Mireya Thalia Putriardi; Sukarmin Sukarmin; Elvin Yusliana Ekawati (Jurnal Materi dan Pembelajaran Fisika, 2023)
Misconceptions that exist in students must be addressed immediately because it will have an impact on further higher learning. This study aims to determine the profile of student misconceptions and the effect of using the Learning Cycle 5E model on reducing the level of misconceptions in Static Fluid material. In the form of descriptive qualitative research with the subject of students of class XI IPA 2 at SMAN 8 Surakarta, totaling 32 students. The treatment given is by giving an initial diagnostic test (pretest) to determine the student's misconception profile, then students are given learning using the Learning Cycle 5E model, and given a final diagnostic test (postest) to determine the decrease in the level of student misconceptions after remediation learning. Data were obtained through a three-stage misconception diagnostic test. The first stage of the diagnostic test was in the form of multiple choice questions, the second stage was in the form of reasons from the first stage questions, and the third stage was to identify students' confidence level. The data analysis technique used was descriptive statistics. The results showed that students had misconceptions on the concepts of the Main Law of Hydrostatics, Pascal's Law, Archimedes' Law, capillary symptoms and viscosity. Based on data analysis, 67.71% of students had misconceptions before remediation learning. After remediation using the Learning Cycle 5E model, the misconceptions experienced by students decreased to 31.94%. The shrinkage of the percentage of student misconceptions experienced was 33.85%. Based on the decrease in the percentage of students who experience misconceptions, it can be concluded that the Learning Cycle 5E model can reduce the level of student misconceptions in Static Fluid material.